Effect of different oestrus synchronization protocols on the reproductive efficiency of Dammar indigenous ewes in Yemen during winter - Hesam, Nasser Saleh Obad; Haron, Abd Wahid; Saharee, Abdul Aziz; Abu Bakar @ Zakaria, Md Zuki; Goriman Khan, Mohd Azam Khan; Jabbar, A. G.; Mahfoz, M. A. (Academic Journals, 2012)
This study compared the effect of oestrus synchronization using controlled-internal-drug-release-device (CIDR) and equine chorionic gonadotropin (eCG) on reproductive efficiency of Dammar ewes in winter. Data of forty-one ewes were divided into two groups; for long CIDR treatment (12 days, LT, n=25) and for short CIDR treatment (6 days, ST, n=16). The LT group was further divided into 3 subgroups to receive eCG either 48 h before CIDR removal (LT1), or at CIDR removal (LT2). Nevertheless, a third subgroup (LT3) received no eCG and served as the control variable. The ST group was also divided into two subgroups to receive eCG either at CIDR removal (ST1) or to receive no eCG (ST2). Five fertile rams naturally mated the ewes. Then in terms of oestrous responses, the pregnancy and lambing rates were 100 percent (100%) in ewes for all treatments. The onset and duration of oestrous was shorter in LTa1 than the remaining subgroups. Litter size in those of LT2 and LT1 subgroups was greater than those of LT3. Additionally, litter size in those of ST1 was greater than in those of ST2 subgroup. This indicated that eCG injection affected litter size. In conclusion, these results indicated that CIDR could successfully be used for either 6 or 12 days prior to ram introduction without having to administer eCG. However, eCG is important to induce multiple births.